1995
DOI: 10.1152/ajprenal.1995.269.3.f389
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular glucose reduces the responsiveness of mesangial cell ion channels to angiotensin II

Abstract: Abnormal cellular ion homeostasis is a well-recognized component of diabetic glomerular disease. In cultured rat glomerular mesangial cells, we have previously shown that insulin regulates Ca(2+)-dependent activation of 4-pS Cl- channels and 27-pS nonselective cation channels (NSCC) by angiotensin II (ANG II). To assess whether extracellular glucose also affects mesangial ion channels, we applied patch-clamp techniques to cells incubated in constant insulin (100 mU/ml) and either "normal" (5 mM) or "high" (30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Recent work in human mesangial cells from our laboratory confirmed direct control of Ca 2 + influx by activated PKC, even in the presence of intact Ca 2 + stores [48]. Interestingly, also the electrophysiology studies by Seal et al [46] indicated that PKC inhibition restores channel responsiveness to angiotensin II in the presence of high glucose [46]. This finding points to a general inhibitory activity of PKC on multiple Ca 2 + transport functions, ranging from the above-mentioned release from intracellular stores, to plasma membrane channels [45,46], to Na + /Ca 2 + exchange in our previous studies [49].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Recent work in human mesangial cells from our laboratory confirmed direct control of Ca 2 + influx by activated PKC, even in the presence of intact Ca 2 + stores [48]. Interestingly, also the electrophysiology studies by Seal et al [46] indicated that PKC inhibition restores channel responsiveness to angiotensin II in the presence of high glucose [46]. This finding points to a general inhibitory activity of PKC on multiple Ca 2 + transport functions, ranging from the above-mentioned release from intracellular stores, to plasma membrane channels [45,46], to Na + /Ca 2 + exchange in our previous studies [49].…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, also the electrophysiology studies by Seal et al [46] indicated that PKC inhibition restores channel responsiveness to angiotensin II in the presence of high glucose [46]. This finding points to a general inhibitory activity of PKC on multiple Ca 2 + transport functions, ranging from the above-mentioned release from intracellular stores, to plasma membrane channels [45,46], to Na + /Ca 2 + exchange in our previous studies [49]. Such inhibition may represent an endogenous negative feedback, aimed at limiting the state of activation of the cells in the presence of vasoconstrictors, and preventing [Ca 2 + ] i from rising to uncontrolled levels.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, reduced contractile responsiveness of mesangial cells to vasoconstrictive peptides, such as angiotensin II, might be related to the development of glomerular hyperfiltration (47). A reduction of both the production of inositol 1,4,5-trisphosphate and the increase in intracellular Ca 2+ in response to angiotensin II was found in mesangial cells cultured under high glucose conditions (48,49); this reduction was shown to be prevented by an inhibition of PKC (49,50). These results strongly suggest that the activation of the PKC-ERK pathway in diabetes is responsible for the development of glomerular hyperfiltration and that troglitazone is able to prevent glomerular hyperfiltration by inhibiting the activation of the PKC-ERK pathway.…”
Section: Discussionmentioning
confidence: 99%